Moderasi Beragama sebagai Fondasi Ajaran Islam dalam Al-Qur’an dan Hadist: Religious Moderation as the Foundation of Islamic Teachings in the Qur'an and Hadith - Afra Sofinatunnajah (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This article discusses the theological basis of religious moderation (al-Wasathiyah), which is sourced directly from the Qur'an and Hadith. Religious moderation is defined as a balanced (tawazun), just (i'tidal), and tolerant (tasamuh) religious attitude, while avoiding all forms of extremism (ghuluw) and neglect (tafrit). This research uses a descriptive method with a literature review approach, analyzing primary and secondary sources, including Qur'anic verses, hadith, tafsir books, academic books, and relevant journal articles. This concept is deeply rooted in the fundamental teachings of Islam and is not a newly emerged ideological compromise. Analysis of key verses, such as Q.S. al-Baqarah: 143, which refers to Muslims as ummatan wasathan (the middle people), and hadiths regarding the prohibition of ghuluw (excess), shows that wasathiyah is a fundamental identity of Muslims and a method of da'wah of the Prophet Muhammad SAW. The values ??of moderation emphasize the importance of justice (al-'adl), balance (tawazun), tolerance (tasamuh), and deliberation (shura). The application of wasathiyah is crucial in global and national contexts for building social harmony, combating radicalism, and addressing the spectrum of extreme religious understandings (radicalism to liberalism). In the educational context, religious moderation is integrated into Multicultural Islamic Education as a systematic effort to instill the values ??of the middle path (wasathiyah) to shape just, balanced, and tolerant students.